Understanding Compliance with COVID-19 Health Protocols: Insights from Barangay Residents in Northern Mindanao, Philippines - Araune, Paolo (Alta Dharma Publisher, 2024)
Background & Aim: The COVID-19 pandemic drastically altered daily life, prompting stringent health protocols globally. Despite progress in vaccination efforts and adaptation to new norms, the pandemic's end remained uncertain. This study investigated the perception and compliance with COVID-19 health protocols among barangay residents in Northern Mindanao, Philippines. Grounded in understanding socio-demographic influences, knowledge, perception, and information sources, the research aimed to discern factors shaping compliance with COVID-19 protocols, informing targeted interventions to enhance public health outcomes. Methods & Materials: This quantitative study employed a descriptive survey research design to evaluate compliance with COVID-19 health protocols among barangay residents in Northern Mindanao, Philippines. Using a sample size of 372 respondents determined by the Cochran formula, data on compliance levels were collected through validated survey questionnaires. Statistical analyses, including the t-test and f-test, were conducted to compare compliance levels across variables such as age, gender, education, and perception of COVID-19 health protocols. Results: Most respondents were 25 to 29, with more females participating. Compliance with COVID-19 health protocols varied significantly by age, gender, educational attainment, sources of information, knowledge, and perception. Specifically, older age groups, females, college graduates, and those with better knowledge and perception demonstrated higher compliance. Conclusion: The findings highlighted the diverse factors influencing compliance with COVID-19 health protocols among residents of a specific barangay in Northern Mindanao. Tailored interventions are imperative to enhance adherence to these measures, offering valuable insights for public health authorities and educational institutions striving to promote community health. Recommendation: This study underscores the importance of targeted interventions and tailored educational efforts to bolster adherence to public health measures, providing crucial guidance for improving community health outcomes.